2021
DOI: 10.1111/os.13165
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparative Study of Pedicle Screw Fixation via Quadrant Retractor and Buck's Technique in the Treatment of Adolescent Spondylolysis

Abstract: Objective To compare the effectiveness and practicality of pedicle screw fixation via the Quadrant retractor and Buck's technique in the treatment of adolescent spondylolysis. Methods A total of 31 patients who underwent pedicle screw fixation or Buck's technique at our hospital from 2012 to 2017 were selected for this retrospective study. The patients were divided into a pedicle screw group (16 patients) and a Buck's technique group (15 patients) according to surgical procedure. Age, sex, disease duration, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Widi et al [7] reported mean duration of 65 minutes (range, 55-80 minutes) for surgery performed based on the percutaneous direct pars repair technique. Ghobrial et al [8] reported mean duration of 189±29 minutes for the direct pars repair technique, based on minimally invasive approach, whereas Li et al [9] described mean surgery time of 216.67±62.60 minutes for procedure based on the conventional Buck technique. Surgeon's experience with endoscopic procedures, and the fact that minimally invasive techniques require shorter surgical time, are some of the explanations for the herein addressed difference in surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…Widi et al [7] reported mean duration of 65 minutes (range, 55-80 minutes) for surgery performed based on the percutaneous direct pars repair technique. Ghobrial et al [8] reported mean duration of 189±29 minutes for the direct pars repair technique, based on minimally invasive approach, whereas Li et al [9] described mean surgery time of 216.67±62.60 minutes for procedure based on the conventional Buck technique. Surgeon's experience with endoscopic procedures, and the fact that minimally invasive techniques require shorter surgical time, are some of the explanations for the herein addressed difference in surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…In lesions that are expected to have a particularly low rate of bone union as they have many negative factors for bone union, if conservative treatment failed to achieve bone union, pain control with oral painkillers or interventional pain injections, early surgery due to pain, or repair surgery for lesions that became pseudoarthrosis may be effective depending on age and sports level [ 6 8 , 22 25 ]. To further develop the treatment of lumbar spondylolysis, prospective studies on the ability to predict the rate of bone union at the time of the initial visit are a future prospect and challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Buck provided one of the first descriptions of bilateral screw fixation across the pars interarticularis defect [39]. Advantages of Buck's technique include preservation of segment motion, rapid postoperative recovery, and minimal blood loss [40]. Further studies detailing utilization of Buck's technique demonstrated satisfactory results in 78-90% of patients [41].…”
Section: Surgical Repair Indicationsmentioning
confidence: 99%